PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) UNTUK GURU PAUD DI KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR PROPINSI RIAU - Alucyana; Sari Herlina; Dian Tri Utami (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
This community service activity aims to increase the knowledge of PAUD teachers in Kampar Kiri Hilir District, Kampar Regency, Riau Province about Classroom Action Research (PTK) so that the quality of learning can be improved as well as self and career development for PAUD teachers. The implementation method for community service activities in Kampar Kiri Hilir District, Kampar Regency, Riau Province includes: (1) Planning Stage. (2) Action Stage, (3) Observation Stage and (4) Reflection Stage. Through PTK teachers can develop teaching models that vary in dynamic and conducive classroom management and the use of appropriate and adequate media and learning resources. Even though the need for implementing Classroom Action Research is very large, not all teachers understand how to implement this activity. This problem is the main problem experienced by Partners, namely PAUD teachers in Kampar Hilir District, Kampar Regency, Riau Province. The solution provided is to conduct training for PAUD teachers on how to make PTK starting from the Preparation, Implementation and Reporting and Scientific Publication stages. The output target to be achieved from this Community Service is to be published in electronic mass media and the Community Service Journal. The plan for this activity is carried out in the form of an initial survey activity at Partner's place, the lecture method and CAR implementation training.